KELENTINGAN PENGHIDUPAN RUMAH TANGGA EKS BURUH HARIAN LEPAS PERKEBUNAN KELAPA SAWIT DI DESA SEI MANGKEI - Ringgo Arman; Hariyadi Hariyadi; Setyawan sunito (Universitas Medan Area, 2017)
The landscape changed of palm oil plantation PTPN III (Persero) Afdeling I became The Sei Mangkei Special Economic Zone (SEZ), it gaves essential impact to the basic problems divided the households livelihood of casual workers (BHL) palm oil plantation in the Sei Mangkei village. This study was illustrated the resilience of the BHL households livelihood in the Sei Mangkei village. This paper aims to measured community resilience of a landscape changed afdeling I PTPN III (Persero) to divided Sei Mangkei SEZ. Analysis of livelihood resilience used a concept of rules is called an index, resilience indicators and households resilience were then collected through questionnaires. The respondent are many 30 BHL households, the sampling located at Sei Mangkei Village. From the calculation of the index has been obtained that result households resilience index a value of 0,35. That means livelihood resilience of BHL household is low when there has been a landscape change at afdeling I divided Sei Mangkei SEZ